Langkawi residents’ dining preferences: a behavioural study of local restaurant patronage / Nur’Alia Natasya Mohd Khasmi ... [et al.] - Mohd Khasmi, Nur’Alia Natasya; Mohamad Saber, Joesri; Sharullain, Nur Shafida; Salim, Azlan; Mahat, Fadhlina; Ibrahim, Mohd Zool Fadli (Universiti Teknologi MARA, Perlis, 2025)
This study investigates the factors influencing Langkawi residents' intentions to patronise local restaurants amidst the challenges and opportunities posed by the island’s tourism and culinary landscape. With the Theory of Planned Behaviour (TPB) as the guiding framework, this research aims to understand how attitudes, subjective norms, and perceived behavioural control impact residents’ dining preferences. A quantitative approach was employed by utilising a structured questionnaire distributed online to 188 Langkawi residents, focusing on factors such as attitudes toward local dining, social influences, and perceived accessibility. Key findings reveal a strong positive correlation between patronising intentions and subjective norms, suggesting that social and cultural factors significantly drive dining choices. Attitudes and perceived behavioural control also strongly predict intentions, indicating that positive perceptions of local cuisine and ease of access encourage patronage. These insights offer practical implications for local restaurant operators, suggesting that fostering positive community attitudes, enhancing social engagement, and improving accessibility could boost local support for dining establishments. However, limitations include the study’s geographic focus on Langkawi and the cross-sectional nature of data, which may limit generalizability. Future research could explore the impact of tourism dynamics and economic changes on local dining behaviours. This study contributes to understanding consumer behaviour within a localised food and beverage sector, providing valuable guidance for stakeholders to enhance the sustainability and competitiveness of Langkawi’s restaurant industry.